Pengaruh Der, Tato Terhadap Nilai Perusahaan Perbankan Di Bursa Efek Indonesia - Maksum, Maksum (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
This study aims to determine the influence of DER and TATO on the Size of Banking Companies measured using ROA. The independent variables are DER and TATO, while the dependent variable is ROA. The sample in this study consists of 4 banking companies listed on the Indonesia Stock Exchange with an observation period from 2014 to 2022. The results show that the DER variable has a significant negative effect on the Size of Companies, with a level of influence of 182.8%. Meanwhile, the TATO variable has a positive but not significant effect on the Size of Companies, with a level of influence of 38.3%. And DER and TATO jointly influence the Size of Companies by 65.8%.